Mycorrhizal Root Colonization, P Uptake, and Yield of Ipomea Reptans Poir. as Affected by Arbuscular Mycorrhizal Fungi and NPK Fertilizer Grown on Andisols - Nurbaity, Anne; Mbusango, Amin (Journal of Tropical Mycorrhiza, 2024)
Andisols have very high P retention so that soil needs to be improved through the application of Arbuscular Mycorrhizal Fungi (AMF) biofertilizers. The aim of the experiment was to determine the effect of AMF and rate of NPK on the root colonization, phosphate uptake, fresh weight of shoot and root of kangkong (Ipomea reptans Poir) on Andisols, it was also aimed to reduce the use of NPK fertilizers. The experiment was conducted in screen house Lembang, West Java. The experiment was arranged with Split Plot Design with AMF as the main plot (with and without AMF) and rate of NPK as subplots (0, 25, 50, 75, and 100% recommended dose). Results showed that there was an effect between AMF and NPK on root colonization, P uptake, fresh weight of shoot and root of kangkong. In general, AMF treatment had a significant effect in increasing root colonization, phosphate uptake, fresh weight of shoot and root of kangkong compared to the treatment without AMF. AMF and 50% NPK treatment showed the best effect on yield of kangkong, hence application of AMF has potential to reduce the use of NPK fertilizer by 50% and increase the productivity of kangkong in Andisols.